KEMAMPUAN KOMUNIKASI ANAK AUTIS DALAM BERINTERAKSI SOSIAL DI SEKOLAH LUAR BIASA KARYA TULUS KOTA MEDAN - Rizky Chairunnisyah; Sori Monang (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) AMIK Indonesia, 2023)
The presence of children in family life is a source of true happiness for married couples. Her greatest hope rests on the growth of her child. However, there have also been a few births of children that families did not expect, especially those with neurological disorders such as autism that impair sensory integration. The purpose of this study was to measure the communication skills of children with autism in social interactions in the Special School of Kariya Turus (SLB)-C, Medan City. The method used is a qualitative research method that uses targeted sampling techniques to select samples according to researchers. Three autistic children, namely KM, S and BS, were included, and two other informants, Veronica Ginting and Masuda Bula Matanari, participated as class teachers. Data collection techniques are carried out through observations, interviews, and documentary research. This work uses Herbert Blumer's symbolic interaction theory. The results showed that she was the only one in three of her subjects who was recognized as having the ability to successfully interact socially. KMs are interactive in their social interactions with researchers, such as reading, writing, counting, and following commands. However, S and BS show deficits in social interaction. They showed no stability in eye contact and were not very cooperative in answering the researchers' questions.